Analisis Status Gizi dengan Screening Stunting di Desa Potronayan, Boyolali - Suryono, Yusuf Ade; Dzakiyyatu Husna, Qisty; Sari Putri Angraini, Mufita; Zaki Faishol Faruq, Muhammad; Indriaputri, Lydia; Suseno, Bayu (PELITA NUSA TENGGARA, 2024)
Nutritional status reflects the adequacy of nutritional needs met through food and drink intake. Stunting is a complex nutritional issue influenced by various factors, including inadequate nutritional intake, poor environmental hygiene, and inappropriate feeding practices. This study aims to assess the nutritional status of children and identify the prevalence of stunting in Potronayan Village. The stunting screening method was employed to gather data on the toddler's age, height, weight, upper arm, and head circumference. The research involved 35 children aged 6 months to 4 years and 4 months. The results based on weight-for-age (W/A), height-for-age (H/A), and weight-for-height (W/H) indices indicate that 91% of the toddlers are of normal weight, while 3% are categorized as very underweight, underweight, or at risk of being overweight. For height-for-age, 77% of the toddlers are of normal height, 17% are classified as stunted, 6% as severely stunted, and none fall into the tall category. Regarding weight-for-height, 91% of the children are well-nourished, 3% are malnourished, 3% are at risk of over-nutrition, 3% are over-nourished, and there are no cases of obesity or severe malnutrition. These findings underscore the need for targeted interventions to address nutritional deficiencies and promote optimal growth and development among children in Potronayan Village.